Emotional Intelligence and Conflict Management Capabilities in Prisoners in Prisons - Nadya Nadya; Ali Ameer; Zaamil Zaamil (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
The purpose of this research is researchers want to see the relationship between emotional intelligence and conflict management abilities in prisoners at the Class II B Batusangkar detention house. The research method used is quantitative with the type of correlational research. The population in this study were prisoners in November 2020, 75 prisoners. The author uses a Likert scale to obtain the required data on emotional intelligence and conflict management skills. The results showed a significant relationship between emotional intelligence and conflict management abilities of prisoners in the Class IIB Batusangkar Detention Center. This is evidenced by the results of the correlation test that recount is greater than the table, thus it can be concluded that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. This means that emotional intelligence is related to conflict management skills.